2010
DOI: 10.3109/01902141003721457
|View full text |Cite|
|
Sign up to set email alerts
|

Semi-fluorinated alkanes as carriers for drug targeting in acute respiratory failure

Abstract: Partial liquid ventilation (PLV) with perfluorocarbons may cause pulmonary recruitment in acute lung injury (ALI). Semi-fluorinated alkanes (SFAs) provide biochemical properties similar to perfluorocarbons. Additionally, SFAs are characterized by increased lipophilicity. Therefore, SFA-PLV may be considered for deposition of certain therapeutic drugs into atelectatic lung areas. In this experimental study SFA-PLV was evaluated to demonstrate feasibility, pulmonary recruitment, and efficacy of drug deposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Basically, at this point, all studies evaluating SFAs as drug-delivery carriers confirmed that SFAs could be used as drug carriers in future lung applications [11,25,26,112].…”
Section: Sfa As Drug Carriers In Acute Respiratory Distress Syndrome ...mentioning
confidence: 69%
See 4 more Smart Citations
“…Basically, at this point, all studies evaluating SFAs as drug-delivery carriers confirmed that SFAs could be used as drug carriers in future lung applications [11,25,26,112].…”
Section: Sfa As Drug Carriers In Acute Respiratory Distress Syndrome ...mentioning
confidence: 69%
“…Dembinski et al were the first research group to report PLV with SFA [11]. This study demonstrates the feasibility of PLV with the SFA perfluorohexyloctane (F6H8) in an (animal) experimental model of ALI and evaluates lung recruitment effects as a function of the SFA dose used.…”
Section: Sfas In Partial Liquid Ventilationmentioning
confidence: 76%
See 3 more Smart Citations